Design a web application using C# programming - Mohammad Saat, Muhamad Norhilmi (2006)
This paper presents a design of a website by using C# programming. C# is an objectoriented programming language that combines both the C++ and the Visual Basic programming. C# is based on C++ and it's contain are almost similar with Java. This project is to utilize IT technology such as the internet to help graduate's student to find a profession in the field of their preferences'. Database is a collection of related information stored in an organized way. With the help of database system, graduate's student can send their resume direct to the company or to the career recruitment agencies for applying an interview via online. This whole process will make easier to both parties. Students and the companies can save a lot in terms of time and money.